Mechanistic Insights into Heterocyclic Diels–Alder Reactivity and Selectivity - Feng, Yixuan (Transactions on Environment, Energy and Earth Sciences, 2026)
Heterocyclic dienes such as furan, pyrrole, and thiophene expand the synthetic versatility of the Diels–Alder (DA) reaction but often deviate from classical Frontier Molecular Orbital (FMO) predictions. Small endo–exo gaps, dearomatization penalties, and retro-DA pathways render outcomes highly sensitive to subtle physical factors beyond orbital symmetry. This review synthesizes recent advances by employing the activation strain model (ASM) and energy decomposition analysis (EDA), complemented by natural orbital for chemical valence (NOCV) channel analysis and transition-state asynchronicity (Δr_TS). Comparative studies benchmark carbocyclic versus heterocyclic systems, quantify substituent and positional effects, and map catalytic modes—including Lewis acids, hydrogen-bond donors, and ion-pair catalysts—onto Δ(ΔE_Pauli/ΔV_elstat/ΔE_orb). Case studies, particularly the furan–maleic anhydride manifold, reveal that endo control in benchmarks is largely strain-dominated, whereas rate modulation in heterodienes frequently originates from Pauli-repulsion reduction and asynchronous transition states. A harmonized framework addressing solvent, temperature, reference state, free versus electronic energies, intrinsic reaction coordinate validation, and conformer handling is presented, together with a unified comparison table. The resulting guidelines connect mechanistic insights to rational design in synthetic, pharmaceutical, and materials chemistry, while identifying priorities for future research.